Considerations on the Classification of Imitation Words (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Since the beginning of the study of imitative words in the Uzbek language, their internal structural division into two groups, imitative words for sound and imitative words for state, has been studied. The article analyzes and justifies the internal structural division of imitative words by adding a third section, the section on imitative words for language units.